Geochemistry of meta‐sediments from Neoproterozoic Shimla and Chail Groups of Outer Lesser Himalaya: Implications for provenance, tectonic setting, and paleo‐weathering conditions. (6th June 2021) - Joshi, Kumar Batuk; Ray, Soumya; Ahmad, Talat; Manavalan, Satyanarayanan; Aradhi, Keshav Krishna
Abstract : The depositional history of the Himalayas has been overprinted by the tectonic activities during the Himalayan Orogeny. A detailed investigation of the sedimentary units can provide crucial information regarding their depositional history and provenance. This study aims at constraining the weathering history, tectonic setting, and provenance of meta‐sediments from the Shimla and Chail Groups of Outer Lesser Himalaya. With similar major element chemistry, these meta‐sediments comprise a low‐silica group (avg. SiO2 /Al2 O3 <3.29). Weathering intensity parameters chemical index of alteration (CIA), plagioclase index of alteration (PIA) and index of chemical variability (ICV) range from 62 to 78 (avg. = 69.41), 70 to 96 (avg. = 85.34), and 0.45 to 1.45 (avg. = 1.01), respectively indicating moderate to severe degrees of weathering. Transition element ratios [Cr/V (1.68–5.18), Ni/Co (1.47–30.99), and V/Ni (0.87–4.61)], and trace element bivariate plots suggest a recycled, felsic to intermediate provenance that has primarily been derived from Post‐Archean sources with minor inputs from Archean units. A passive margin depositional setting with arc‐derived sources is suggested for the Chail and Shimla meta‐sediments. Rare‐earth element patterns reveal similarities between the studied metasediments with TTG gneisses and sanukitoids from the Aravalli and Bundelkhand Cratons, as well as Chaur and Jutogh granitoids. Therefore, Neoproterozoic Himalayan granitoids and Archean Aravalli‐Bundelkhand granitoids (TTGs and high‐K granitoids) could be potential sources of these meta‐sediments, as also suggested by the detrital zircon age distribution from the Beas‐Satluj‐Pabbar valleys and Shimla Group. Abstract : This study aims at constraining the weathering history, tectonic setting, and provenance of meta‐sediments from Shimla and Chail Groups of Outer Lesser Himalaya. Transition element ratios and trace element bivariate plots suggest a Late‐Archean to Post‐Archean source felsic to intermediate source. With geochemical characters more aligned with Post Archean upper continental crust, these meta‐sediments have been derived primarily from the Post‐Archean sources with minor inputs from Archean units. Neoproterozoic Himalayan granitoids and Archean Aravalli‐Bundelkhand granitoids (TTGs and High‐K granitoids) could be potential sources of these meta‐sediments as also suggested by the detrital zircon age distribution from the Beas‐Satluj‐Pabbar valleys and Shimla Group.